INTERNATIONAL JURISDICTION IN DISPUTES OVER INFRINGIMENT OF PERSONALITY RIGHTS ON THE INTERNET – SERBIAN AND EU LAW - Đundić, Petar (Zbornik radova Pravnog fakulteta u Novom Sadu, 2023)
Invention and wide-spread use of the internet pose particular challenges for Private International Law. Ubiquitous nature of content placed online, the fact that internet-users are able to create the content themselves and the absence of any meaningful geographic connection between transactions conducted online and a territory of any given country are factors which are, on the one hand, increasing the number of cases with cross-border implications while, as the same time, rendering the use of traditional rules of jurisdiction and choice of law increasingly difficult. This is particularly the case with cross-border infringements of personality rights via the internet. The paper discusses the issue of jurisdiction for this particular category of internet-torts. Based on the analysis of the case law created by the Court of Justice of the European Union and the practice of courts in certain national jurisdictions, the author concludes that a reasonable and purposeful interpretation of the notion “place of damage” as a criterion of special jurisdiction for torts used in Article 53(1) of the Serbian Private International Law Code, entails that for the acceptance of jurisdiction by Serbian courts it is not enough that the relevant content is accessible from the territory of Serbia. It is also necessary that a victim’s habitual residence or main place of business is in Serbia. Such interpretation allows Serbian courts to accept jurisdiction in circumstances in which there is a real and meaningful connection of a dispute with Serbia, provides the plaintiff with efficient legal protection of his rights and guarantees the defendant a reasonable opportunity to foresee a competent forum.
Keywords: internet-torts, infringement of personality rights, international jurisdiction of courts, the place of harmful event, the place of damage.